From the information in the table providing values of f(x) and g(x), evalute (FoG)^-1(3). Table: x 1 2 3 4 5 f(x) 5 3 5 1 2 g(x) 4 5 1 3 2 My answer is 4, but not sure, thanks for any help given.
Follow Math Help Forum on Facebook and Google+
Originally Posted by kwtolley From the information in the table providing values of f(x) and g(x), evalute (FoG)^-1(3). Table: x 1 2 3 4 5 f(x) 5 3 5 1 2 g(x) 4 5 1 3 2 My answer is 4, but not sure, thanks for any help given. If $\displaystyle x=(f\circ g)^{-1}(3)$, then $\displaystyle (f\circ g)(x)=3$, or: $\displaystyle f(g(x))=3 $, $\displaystyle g(x)=f^{-1}(3)=2$ $\displaystyle x=g^{-1}(2)=5$. RonL
thanks I thought I was wrong.
View Tag Cloud